REDESIGN USER INTERFACE APLIKASI IPUSNAS BERDASARKAN USER EXPERIENCE DENGAN METODE DESIGN THINKING - Intan Tresna Lestari; Dian Permata Sari; Rian Andrian (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
: User Interface redesign is the process of redesigning an existing design with the aim of improving application performance and user experience. The purpose of redesigning the iPusnas application user interface is to improve the User Interface design according to user needs based on real user experience. This is in order to improve the quality of the iPusnas application to be better in terms of the User Interface and User Experience. This redesign was carried out by means of collecting documentation data, where the method of searching for data related to research. The authors took these data from reviews of the iPusnas application on one of the store application platforms, namely the Play Store, because judging by the reviews or feedback given by some users to the iPusnas application, it requires an improvement, both in terms of features, or appearance design. . The system development method used in the redesign process for this iPusnas application is the Design Thinking Method. Design Thinking is a design method that provides a solution-based approach to solving problems. That way, the design thinking method is considered very suitable for the application redesign development process, because with this method, we can understand the user's needs. Based on the test results on the redesign of the iPusnas application prototype, the redesigned prototype is fairly understandable by users, judging from the rating given by 5 testers with an average of 5 and 4.2 out of 5 with very easy descriptions. Therefore, the UI design redesign process based on UX is fairly good where users can complete the flow easily. With the redesign of the iPusnas application, it is hoped that it can improve the quality of the performance of the iPusnas application itself, both in terms of the User Interface or in terms of User Experience.